Hubungan antara Empati dan Konformitas Teman Sebaya dengan Perundungan Verbal Siswa - Yuliana Yuliana; Muslikah Muslikah (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2021)
Based on the preliminary study that has been conducted, verbal bullying among junior high school students still occurs frequently. Verbal bullying is often done, such as mocking other students' appearance, body shape, and speech style. This study aims to determine the relationship between empathy and peer conformity with verbal bullying of students at SMP Negeri Semarang City. This research method uses a quantitative correlational design, the sampling uses purposive and random sampling with a total of 243 respondents. The analysis technique uses multiple regression analysis with the help of the SPSS version 23 application. Based on the results of multiple regression analysis, it shows that empathy and peer conformity jointly have a relationship with verbal bullying with a simultaneous F significance value of 0.000 (sig <0.05) and F count 19,740, and F table 3.03 (Fh> Ft). The contribution of empathy and peer conformity variables was 14.1% for verbal bullying, while 85.9% was influenced by other factors that were not explained in this study. Based on the results of research above guidance and counseling teacher is expected to provide group guidance services in the private and social field to reduce verbal bullying. The theme that may use is related to the prevention of verbal bullying.